PRIMARY PRODUCTIVITY OF A GRASSLAND COMMUNITY IN RANGAMATIA, MAYURBHANJ, ODISHA - PRAMOD KUMAR KAR (The Bioscan, 2012)
Ecological analysis of a grassland community was carried out at the place of Rangamatia near Similipal Biosphere Reserve, Odisha. The primary productivity in various compartments i.e. live green, standing dead, litter and below ground was studied following the method of Odum (1960). It indicated that the total above ground was maximum during June and minimum in the month of December. Litter compartment did not show any increment during rainy season while the below ground compartment showed higher productivity in rainy season. The total net primary production of the community was found to be 6403.07g m-2 yr-1. The transfer function of above ground net production was 8.09 times higher than that of below ground net production. The turnover rate of non-grasses was found to be maximum as compared to that of grasses. Among the components of the community i.e. live green, standing dead and below ground the turnover rates were not significantly different from each other.